STRATEGI MENINGKATKAN LITERASI DAN MINAT BACA MELALUI PROMOTIONAL MIX DI PERPUSTAKAAN UNNES - Kusumastuti, Dina Nurcahyani; Handoyo, M.Z. Eko (FPPTI Jawa Tengah, 2020)
Libraries have an important role in higher education, especially in research and development activities, innovation, and scientific engineering. This important role, among others, is due to its services in the development and processing, restoration of library materials, in addition to carrying out library administration duties. Besides that, the library also has functions of education, information sources, recreation, publication, and information deposit. However, in its development, these functions have not been carried out optimally by the library, in this case the Semarang State University Library (UNNES). This is because there has been no significant breakthrough, so it seems that the library is only needed when the user (read: student) is working on a thesis or final project as a requirement for graduation. Based on this understanding and by adapting marketing concepts, this paper intends to describe the promotional mix concept and its pplication to increase literacy and reading interest among readers.